Circulating Capital Management and Its Impact on Profitability: Evidence From Selected Food and Beverage Companies Listed in DSE - Ahmed, Md. Razu; Islam, Md. Shajadul; Islam, Md. Dipu; Hossain, Maruf (International Journal of Accounting and Financial Reporting, 2023)
Circulating capital management and its impact on profitability seek an empirical relationship between circulating capital and profitability. The study is based on secondary data collected from the websites of food and beverage companies. Because of the availability of data, this study covers six food and beverage companies from 2016 to 2020. The circulating capital components are cash conversion cycle (CCC), inventory turnover (IT), accounts payable payment period (APPP), accounts receivable collection periods (ARCP), and profitability, which involves return on assets (ROA) and net profit margin (NPM). This study implicates descriptive statistics and inferential statistics, which have analyzed mean, standard deviation, correlation, and regression to summarize the inverse connection between CCC, IT, ARCP, APPP, and ROA. The study also summarizes the significant relationship between CCC, ARCP, and NPM and the insignificant impact of IT and APPP on NPM. I have found both positive and negative connections between circulating capital components and profitability. So, CCC, IT, ARCP, and APPP should be well communicated with ROA and inventory turnover, and the accounts payable payment period should be optimal with NPM.